Identifying Indications for Percutaneous (PTC) vs. Endoscopic Ultrasound (EUS)- Guided „Rendezvous“ Procedure in Biliary Obstruction and Incomplete Endoscopic Retrograde Cholangiography (ERC) - Albert, J. G.; Finkelmeier, F.; Friedrich-Rust, M.; Kronenberger, B.; Trojan, J.; Zeuzem, S.; Sarrazin, C. (Zeitschrift für Gastroenterologie, 2014)
Background: The variety of rendezvous (RV) procedures has recently been extended by EUS- and PTCD-guided procedures as a complementary means to conventional ERCP. We have identified indication criteria and the potential of biliary PTCD-guided vs. EUS-guided RV.Methods: Consecutive patients with bile duct obstruction who underwent RV were included. In all, ERCP alone was unable to achieve treatment success. Indication, technical success, and outcome in PTCD- vs. EUS-guided RV were retrospectively compared to identify criteria that indicate preference of RV technique. Site of obstruction, clinical scenario (stenosis with abscess vs. no abscess) and reason for previous failure of ERC were evaluated.Results: In 32 patients, three different indications for RV procedures were identified: First, a one-step access to assist in failed ERCP (type 1, intra-ductal RV); second, temporary drainage for prolonged treatment of complex biliary disease (type 2, intra-ductal RV), and drainage of cholangio-abscess with re-establishing bile outflow (type 3, intra-abscess RV). Indication of PTCD- vs. EUS-guided rendezvous was competitive in type 1, but exclusive in favor of PTCD in types 2 and 3. The site of biliary obstruction indicated the anatomic location of RV procedures.Conclusions: This classification may help to define inclusion criteria for prospective studies on biliary RV procedures. Choice of therapeutic strategy depends on the anatomic location of the biliary obstruction and the type of the biliary lesion. PTCD-guided RV might improve outcome in cholangio-abscess.
Keywords: Leber; Gallenwege; ERCP; Endoskopie